Water sorption properties of papaya seeds (Carica papaya L.) formosa variety: An assessment under storage and drying conditions. (March 2021) - Rosa, Daniele Penteado; Evangelista, Rodrigo Rodrigues; Borges Machado, André Luiz; Sanches, Marcio Augusto Ribeiro; Telis-Romero, Javier
Abstract: In this research, sorption isotherms and thermodynamic properties of papaya seeds were evaluated by simulating storage and drying temperatures. Papaya seeds and its oil were evaluated for their proximate composition and physicochemical parameters, respectively. Water adsorption isotherms of papaya seeds were determined at seven temperatures (20–80 °C) by the gravimetric-static method. The net isosteric heat of sorption was determined by using Clausius-Clapeyron Equation. The differential enthalpy and entropy and the free Gibbs energy were calculated using the sorption data. The adsorption surface area was determined using the monolayer moisture content obtained from GAB model fitting. Peleg model was selected to describe the sorption isotherms of papaya seeds because it presented great precision ( R Adj 2 > 0.993 and χ 2 ≤0.00031). The equilibrium moisture content of the papaya seeds decreased with increasing temperature. At all temperatures, sorption isotherms exhibited type II sigmoid shape. The net isosteric heat of sorption (0.56–8.71 kJ/mol), differential enthalpy (−8.71 to −0.56 kJ/mol), and entropy (0.08–20.13 J/molK) decreased with the increasing of equilibrium moisture content. The enthalpy-entropy compensation theory was validated. The increase in temperature decreased the value of the surface area of sorption. The process was enthalpy-driven and nonspontaneous (+ ΔG B ) . Highlights: The papaya seeds and its oil were characterized. The sorption isotherms obtained were classified as Type II sigmoid. Peleg's model better described the sorption isotherms in all conditions evaluated. Differential enthalpy and entropy confirmed the isokinetic compensation theory. The adsorption surface area decreased with the increasing of evaluated temperatures.